Análisis de la apropiación y uso de las TIC por parte de las pymes colombianas (2017)
The development and appropriation of ICT (Information and Communication Technologies) has marked the course of the nations as they take on these technologies at all levels. The innumerable benefits and promises of the appropriation of these technologies by the citizens and, above all, of the companies that make up an economy seem to be still waiting.Colombia has not been indifferent to the process of ICT development, throughthe creation of policies and laws aimed at seeking the massification of the use oftechnologies, aimed at both the end user and the productive sector, the country tries to embed itself in demanding processes to deal with of assuming them. The diverse computational and information technologies, are the central axis of the commercial development of the companies; But for the Colombian case the efforts made by the last governments have not yielded the expected results, especially in the case of small and medium-sized enterprises (SMEs), as confirmed by the present investigation.